Space and Affect: Using Heidegger to Re-interpret the Disability Experience - Josephine A. Seguna (Disability Studies Quarterly, 2015)
Space, a vital element of contemporary social boundaries, has prompted debate into the significance, embodiment, construction of spatiality and the marginality and exclusion of minorities. Such 'disabled' relations' at the intersection of self and other, self and self, and self and objects function through spatial organization and negotiations of power in everyday experiences. Martin Heidegger's interpretation of space (Being and Time, 1927) allows for new considerations of existence in relation to categorization, labelling and exile of those outside mass society. Human existence is not one of subjectivity but rather the nature of the world through 'Space' as a condition of individual experience and inclusive of all aspects of Dasein's Being-in-the-world-with-others. This paper, using Heidegger's analysis, highlights social interaction and construction of disability as a product of interpretive processes, creating and maintaining division between 'normal and other' and thus ignoring the possibility of conceiving disability as a legitimate, valued embodied difference. Keywords: Spatiality, Heidegger, Disability, Ableism, Critical Disability Studies
Keywords: Spatiality; Heidegger; Disability; Ableism; Critical Disability Studies